Dinâmica temporal e composição florística da comunidade arbórea de floresta ombrófila densa montana, Parque Estadual da Serra do Mar, SP, Brasil - Renó, Isabela Porto [UNESP] (2015)
The Atlantic Forest is the second largest tropical rainforest in the Americas but today they remain about 15% of its original vegetation and are essential studies of its remaining for providing valuable information for their conservation. In the Atlantic Forest (Rain Forest) is included vegetation type of the Atlantic rain forest Montane, where the climate is cooler, at altitudes ranging from 500 to 1000 m, but studies of this vegetation are scarce. To enhance understanding about Rain Forest Montana Serra do Mar region (SP), through the structure, temporal changes and floristic composition, the study aims to describe and analyze (a) as the components of the structure and dynamics of tree communities vary in time, (b) how these changes may vary in space and (c) how the floristic composition and similarity between nearby areas. The analysis of the structure and dynamic data were performed using the database containing three censuses, which occurred from 2007 to 2012 (about five years) in four plots (K, L, M and N). Regarding the temporal and spatial changes in the structure of Montane forest, there was a decrease in the density of individuals between censuses, with few differences even between plots; between life forms the trees had higher density than palm trees. Was stable in the basal area over time with a few differences between the portions; in relation to the stock of living biomass above soil was increased over time in all plots. The lowest values in density, basal area and biomass were observed for the plot N. Regarding the diameter classes, the community had a higher density in the smaller diameter classes, and lower density in the larger classes, and found the same pattern between censuses all plots, with changes over the census only in the smaller classes. Both forms of life, trees and palms, were significantly different from each other in relation to the structure, with little variation between censuses. In forest dynamics, there...